Smartphones and Changes in Interest in Learning: Perspective of Mts Attaufiq Padaelo Learners - Atty; Amin, Sitti Jamilah; Dalle, Ambo; Marhani; Aminah, St (Jurnal Amal Pendidikan, 2024)
The rapid development of technology has made smartphones an integral part of daily life, offering various benefits such as communication, information access, and educational support. However, excessive use of smartphones among students has raised concerns about its negative impact on academic performance and interpersonal skills. This study aims to analyze the effects of smartphone usage on students' academic achievement and learning interests by identifying both positive and negative implications. The research employs a mixed-method approach, combining surveys and interviews with students to understand their smartphone usage patterns and their influence on their educational outcomes. Results indicate that while smartphones facilitate access to learning materials and foster peer collaboration, their overuse of social media and gaming negatively affects concentration and academic performance. The study concludes that balanced and purposeful use of smartphones can enhance learning experiences, while excessive reliance may hinder students' personal and academic growth.